Experimental microablation of choroidal tissue for autologous retinal pigmentepithelium–choroid translocation with the pulsed electron avalanche knife (PEAK-fc). Issue 10 (28th May 2010) - Treumer, Felix; Sattler, Benjamin; Bunse, Arnd; Klettner, Alexa; Hillenkamp, Jost; Roider, Johann
Abstract : Aim: To test the microablation of excess graft choroidal tissue with the pulsed electron avalanche knife (PEAK-fc) in an in-vitro model of autologous retinal pigment epithelium (RPE)–choroid translocation. Methods: Choroidal tissue of porcine RPE–choroid explants was ablated with the PEAK-fc. Tissue morphology was assessed by light microscopy (LM) and scanning electron microscopy (SEM). The amount of ablated choroidal tissue was analysed as a function of three PEAK-fc parameters: (1) amplitude of biphasic voltage (70–100%); (2) distance between choroidal tissue and tip of the PEAK-fc (0–300 μm); and (3) exposure time (2–8 s). Results: LM and SEM showed a smooth plain within the ablation area with well defined cutting edges and preserved adjacent tissue structure. The mean amount of ablated tissue correlated linearly with applied voltage (range 79–120 μm, r=0.34) and distance between choroidal tissue and PEAK-fc tip (range 10–100 μm, r=0.74). The mean amount of ablated tissue increased with exposure time between 2 and 4 s (36–88 μm, r=0.4) and remained constant between 4 and 8 s. Conclusion: The PEAK-fc accurately microablates choroidal tissue in-vitro. The adjacent choroidal tissue structure and Bruch's membrane are preserved. Patient studies are required to test the PEAK-fc in RPE–choroid translocation surgery.